Archivos y sociedad - Añorve Guillén, Martha Alicia (Revista General de Información y Documentación, 2008)
Those, whose work is realted to the organization of archives should ask themselves in the very first place about the purpose of their organization, that is, the role of the archives in our society. International Organizations (UNESCO and ICA- International Council on Archives) have fostered certain “interest” among governments in the preservation, the organization of archives, as well as their integration both, to the knowledge society as well as a part of the human heritage. This “sensibility” is an opportunity that we, the archives professionals, must take advantage of. Despite the fact that society in general has little understanding of the relevance of archivist documentation, the professionals and the academic and researching staff praise their role in the preservation of the collective memory, identity, knowledge’s build-up, our personal life, and accountability.